The psychometric properties of the Arabic version of the Satisfaction with Daily Occupations. (April 2015) - Manee, Fahad; Alotaibi, Naser; Alobaidly, Fatma; Abu Tariah, Hashem; Hamed, Razan; Eklund, Mona
Introduction: There is a shortage of tools designed for use by occupational therapy practice in Arabic-speaking countries. The purpose of this study was to translate and cross-culturally adapt the original Satisfaction with Daily Occupations tool to Arabic and assess the psychometric properties of the adapted tool. Method: A cross-cultural adaptation process was performed. Face, content, and criterion validity were examined, as well as internal consistency and test–retest reliability. The study included 147 healthy adults and 73 patients with cerebrovascular accident. They were purposefully selected from two countries (Kuwait and Jordan). Results: The adapted tool comprised six domains and a total of 14 items. Face and content validity were established through prolonged content analysis. Criterion validity was indicated by significant differences between the healthy and the cerebrovascular accident group in all areas of the Satisfaction Daily Occupations scale ( p  < 0.001). Satisfactory overall internal consistency (α = 0.77) and good test–retest reliability for the total satisfaction score for the healthy (inter-class correlation coefficient (ICC) = 0.984) and the cerebrovascular accident group (inter-class correlation coefficient (ICC) = 0.933) were found. Conclusions: The Satisfaction with Daily Occupations-Arabic version is a valid and reliable tool for use with Arabic-speaking occupational therapy clients. This study has several implications for occupational therapy education, practice, and research in the Arab world.